Design and Construction of a Trolley-Type Paddy Collection and Bagging Machine - ลีละธนาฤกษ์ วสันต์; ศักดิ์บุญญารัตน์ ธัญญพัทธ์; อมรปีติกวิน สุวิทย์; ถนัดรบ เกริกขจร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to design and develop a trolley-type paddy collection and bagging machine to improve the efficiency of harvesting and storage processes. By replacing manual labor with this mechanical picker, farmers can significantly reduce the time required for collecting and bagging dried paddy. This study evaluates the operational efficiency of the machine compared to traditional manual methods. The machine’s structure measures 995 mm in width, 1,370 mm in length, and 1,160 mm in height. It comprises four primary systems: a sweeping unit, a conveyor system, a drive system, and a power transmission set. The sweeping unit features a screw conveyor with a length of 1,000 mm and a diameter of 140 mm. The conveyor system utilizes a 320 mm roller with a 47 mm diameter and a 2,500 mm belt. The drive system is powered by a 500W, 24V DC motor (300 rpm) supported by two 12V batteries. The power transmission set consists of No. 428 sprockets (16/28 teeth) and a No. 428 chain with 74 links. Experimental results indicate that the machine significantly outperforms manual labor. While manual collection took an average of 14.89 minutes, the machine completed the task in just 8.57 minutes a reduction of 6.32 minutes, or 44.53%. The machine achieves a collection rate of 1,260 kilograms per hour, with an estimated payback period of 6 months.